1999
DOI: 10.1097/00042560-199901010-00013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race on Insurance Coverage and Health Service Use for HIV-Infected Gay Men

Abstract: Further research must be conducted to examine cultural, social, and psychological factors that help explain why white gay men use more outpatient and dental services, when other service use is unrelated to race. Investigators should be precise when using race as a variable in health services and epidemiologic research, emphasizing when racial differences truly exist versus when the variable race is a surrogate for another factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…38 In contrast, analysis of data for 1991-1996 found that among 307 men at the Baltimore MACS site, only 43% reported at their most recent study visit having used antiretroviral medications in the prior six months. 43 Another study in Baltimore found among 838 people who presented to the Johns Hopkins AIDS Service in 1990-1992 that 58% of African Americans and 63% of whites reported current antiretroviral use. 39 Somewhat later, in 1993-1995, 70% of 863 HIVpositive women enrolled in the HIV Epidemiology Research Study (HERS) reported ever having used antiretrovirals, but only 43% reported current use.…”
Section: Antiretroviral Usementioning
confidence: 99%
See 4 more Smart Citations
“…38 In contrast, analysis of data for 1991-1996 found that among 307 men at the Baltimore MACS site, only 43% reported at their most recent study visit having used antiretroviral medications in the prior six months. 43 Another study in Baltimore found among 838 people who presented to the Johns Hopkins AIDS Service in 1990-1992 that 58% of African Americans and 63% of whites reported current antiretroviral use. 39 Somewhat later, in 1993-1995, 70% of 863 HIVpositive women enrolled in the HIV Epidemiology Research Study (HERS) reported ever having used antiretrovirals, but only 43% reported current use.…”
Section: Antiretroviral Usementioning
confidence: 99%
“…(See Table 1.) Overall, 15 studies had data collection periods that included 1996 or later, [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] i.e., after FDA approval for use of the first protease inhibitor in late 1995. Ten of the these reports specifically measured the use of either protease inhibitors, NNRTIs, or HAART.…”
Section: Antiretroviral Usementioning
confidence: 99%
See 3 more Smart Citations